2018
DOI: 10.1186/s13662-018-1639-2
|View full text |Cite
|
Sign up to set email alerts
|

On ideal convergence Fibonacci difference sequence spaces

Abstract: The Fibonacci sequence was firstly used in the theory of sequence spaces by Kara and Başarir (Casp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…After that in 1999, Kostyrko et al [22] defined a generalization of statistical convergence, known as I-convergence. Later,Ŝalát et al [29,30], Filipów and Tryba [9] and many others [17,19] further studied the notion of I-convergence and linked with the summability theory. Furthermore, some authors also investigated it from the sequence space point of view.…”
Section: Introductionmentioning
confidence: 99%
“…After that in 1999, Kostyrko et al [22] defined a generalization of statistical convergence, known as I-convergence. Later,Ŝalát et al [29,30], Filipów and Tryba [9] and many others [17,19] further studied the notion of I-convergence and linked with the summability theory. Furthermore, some authors also investigated it from the sequence space point of view.…”
Section: Introductionmentioning
confidence: 99%
“…al [6]. Also, related studies can be found in [13]- [17]. Some new sequence spaces were introduced by means of various matrix transformations in [18], [19], [28] and [35].…”
Section: Introductionmentioning
confidence: 99%
“…where (f n ), n ∈ N is the sequence of Fibonacci numbers given by the linear recurrence relation as f 0 = 1 = f 1 and f n-1 + f n-2 = f n for n ≥ 2. Quite recently, Khan et al [13] defined the notion of I-convergent Fibonacci difference sequence spaces as c I 0 (F), c I (F) and l I ∞ (F).…”
Section: Introductionmentioning
confidence: 99%
“…[13]) A sequence x = (x n ) is said to be I-Cauchy if for every > 0 ∃ a number N = N( ) such that the set {n ∈ N : |x nx N | ≥ } ∈ I.…”
mentioning
confidence: 99%